Flash flood management applied by local authority / Norhuda Mohamed - Mohamed, Norhuda (2008)
Flood is naturally known as one of nature’s occurrence that can be triggered by Act of God and human fault. Besides, flash flood is the disaster that always occurs at the town center affect by the rapid development, drainage and irrigation system and also human fault. Flash flood mitigation is the action measures to reduce the flash flood occurrence. The structural measure divided to structural measure and non-structural measure. In order to reduce the flash flood occurrence, both parties between the government and private parties should take the responsibility to reduce the flash flood occurrence it is because this disaster can give the bad effect in term of the healthy and other that will discuss in Chapter 2 and Chapter 3 Subsequently, this dissertation will explores the causes or factor, the implement action by the Local Authority and also about the effectiveness of the current implementations of flash flood mitigation system and its impact towards the society and economy due to the recurring the flash flood problems.